Impact of exercise on fecal and cecal metabolome over aging: a longitudinal study in rats. (January 2017) - Deda, Olga; Gika, Helen; Panagoulis, Theodoros; Taitzoglou, Ioannis; Raikos, Nikolaos; Theodoridis, Georgios
Aim: Physical exercise can reduce adverse conditions during aging, while both exercise and aging act as metabolism modifiers. The present study investigates rat fecal and cecal metabolome alterations derived from exercise during rats' lifespan.Methods & results: Groups of rats trained life-long or for a specific period of time were under study. The training protocol consisted of swimming, 15–18 min per day, 3–5 days per week, with load of 4–0% of rat's weight. Fecal samples and cecal extracts were analyzed by targeted and untargeted metabolic profiling methods (GC–MS and LC–MS/MS). Effects of exercise and aging on the rats' fecal and cecal metabolome were observed.Conclusion: Fecal and cecal metabolomics are a promising field to investigate exercise biochemistry and age-related alterations.